2002
DOI: 10.1063/1.1459621
|View full text |Cite
|
Sign up to set email alerts
|

Surface-bulk hybrid mode in 36°-rotated YX cut of lithium tantalate with periodic metal grating

Abstract: We report on a surface-bulk hybrid acoustic mode, which exists within a limited frequency interval in some piezoelectric substrates within a periodic metal grating. These hybrid modes result from the coupling between a bulk wave and a counter-propagating surface (or leaky) wave. An example of such a hybrid mode, which propagates in 36°-YX cut of lithium tantalate, is described. The hybrid mode gives rise to an additional branch of dispersion relation. The Bragg reflection stop band occurs due to phase match be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Recently, it was found that in some substrates SSBW builds a surface-bulk hybrid mode (SBH) with SAW or leaky wave [1][2]. It results in parasitic resonances and general deterioration of SAW filter performance.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, it was found that in some substrates SSBW builds a surface-bulk hybrid mode (SBH) with SAW or leaky wave [1][2]. It results in parasitic resonances and general deterioration of SAW filter performance.…”
Section: Introductionmentioning
confidence: 98%